The effect of traditional hygro-thermal pretreatments on the acoustical characteristics of white mulberry wood (Morus alba) - Se Golpayegani, Aida; Brémaud, Iris; Thevenon, Marie-France; Pourtahmasi, Kambiz; Gril, Joseph (Maderas. Ciencia y Tecnología, 2025)
The wood used in making musical instruments usually undergoes pre-treatments or conditioning. Some processes have resulted from laboratory research, while many treatments are applied by craftsmen using traditional methods that have not yet been scientifically assessed. This paper is based on laboratory methods which simulate hydrothermal pre-treatments traditionally applied by Iranian lute makers to mulberry (Morus alba), an important wood for lutes from the Middle East to Japan. By applying a cyclic process, drying (60°C) and ambient re-conditioning, which mimics wood seasoning and short-term aging, the damping coefficient (tanδ) was decreased down to 10% without negatively affecting specific modulus of elasticity (E’/ρ). Long-term (up to 4 months) soaking in cold water removed extractives, and decreased density as well as E’/ρ, but did not affect tanδ. Short-term hot water treatment removed as many extractives, but caused a smaller decrease in E’/ρ than cold water, and significantly increased tanδ. This paper helps to clarify some traditional processes used by instrument makers, and can provide a basis for necessary cross-cultural scientific studies in the future.